2014
DOI: 10.1682/jrrd.2013.01.0011
|View full text |Cite
|
Sign up to set email alerts
|

Health and well-being of homeless veterans participating in transitional and supported employment: Six-month outcomes

Abstract: Abstract-Supported employment, specifically individual placement and support (IPS), improves competitive employment (CE) rates for individuals with serious mental illness, but has not shown greater improvement in non-vocational outcomes than other rehabilitation approaches. The Department of Veterans Affairs offers two types of vocational services, IPS and transitional work experience (TWE), but no study has compared the effectiveness of these approaches. This secondary analysis of data from a study of homeles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 62 publications
1
7
0
Order By: Relevance
“…The VR&E service currently provides employment services to an estimated 4.2 percent of veterans with psychiatric disabilities, including supported employment [53], and evidence demonstrates these services' effectiveness [54]. Our results support a vocational rehabilitation focus on enhancing workers' job satisfaction, helping them secure better paid positions, and providing them with career-building services even after employment to help them keep working or return more easily to work after separation from a job.…”
Section: Discussionsupporting
confidence: 55%
“…The VR&E service currently provides employment services to an estimated 4.2 percent of veterans with psychiatric disabilities, including supported employment [53], and evidence demonstrates these services' effectiveness [54]. Our results support a vocational rehabilitation focus on enhancing workers' job satisfaction, helping them secure better paid positions, and providing them with career-building services even after employment to help them keep working or return more easily to work after separation from a job.…”
Section: Discussionsupporting
confidence: 55%
“…Productivity occupations, such as paid and unpaid employment, are likely to support the social and psychological integration of chronically homeless persons in mainstream society and should be a priority in support models. Individual placement and support (Leddy, Stefanovics, & Rosenheck, 2014), social enterprise (Ferguson, 2007), and supported and transitional employment (Marrone, 2005) have been demonstrated as effective interventions for helping homeless persons return to employment. Few studies have demonstrated the efficacy of employment models for chronically homeless persons.…”
Section: Discussionmentioning
confidence: 99%
“…Frain et al (2010) pointed out that in 2007, between 12% and 23% of women were exposed to trauma in combat areas. Mental health issues can greatly impede African American veterans' participation in employment and career success (Boutin, 2011;Burke, Degeneffe, & Olney, 2009;Leddy, Stefanovics, & Rosenheck, 2014), and female veterans need the expertise of VR to successfully transition into employment (Atkins, 2011). In addition, mental illness has been associated with slower veterans' progress in the VR system (O'Connor et al, 2011).…”
Section: Discussionmentioning
confidence: 99%